Conceptions and misconceptions of hostels worldwide - Somlai , Réka (Applied Studies in Agribusiness and Commerce, 2014)
Present research is inspired to study the conceptions and misconceptions of hostels in eight different countries (Spain, United States, United Kingdom, Germany, Hungary, Venezuela, China, Australia). The outcome of the research reports that the participants in the United States, United Kingdom, Germany and in Hungary define hostels as youth accommodations, Spanish participants as cheap hotels and Venezuelans call them homeless shelters. The majority of the participants of all the above mentioned countries determine that the most important difference between hostels and hotels is the price. Americans, English, Germans, and Hungarians believe that a night would cost between 10 and 30 Euro in an average hostel, while Spaniards and Venezuelans say it would be under 10 Euro. Most respondents agree that hostels are; located in the city center, great places to socialize, offer safe accommodation, staying in there allows guests to save up money, and they are popular choices among travelers. American and English participants think hostels are only for people who like to party. Spaniards and Venezuelans think, hostels are outside of the city center. Spanish and English participants believe that hostels are too cheap to be able to offer a good service. Most participants say, the low price would be the main reason to stay in a hostel. Americans, English and Germans also think that other values are important besides the price: fun, the opportunity to meet people and atmosphere. In spite of all the above, most participants think people would rather stay in a hotel than in a hostel. Stereotypes evolve in different ways, which also explains how misconceptions about hostels developed.